Matrix graphite powder for preparing high-thermal-conductivity fuel element as well as preparation method and application of matrix graphite powder
By using high -purity graphite powder, high -purity needle -shaped scorched powder and high -purity asphalt prepared by the substrate graphite powder, the problem of low base graphite thermal guidance rate in existing technology has been solved, and the thermal guidance rate and anti -resistance of the fuel element have been significantly increased. The oxidation performance improves the performance and safety of high -temperature air -cooled reactors.
Patent Information
- Application Number
- CN202411427481.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-01-24
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the existing high-temperature air-cooled reactors, the thermal conductivity of matrix graphite is relatively low, which is mainly due to the low graphitization and thermal conductivity of artificial graphite and resin binders, which limits the performance of fuel components.
Adopt high -purity and natural graphite powder, high -purity needle -shaped scorched powder and high -purity asphalt as raw materials. High -purity asphalt is used as a binder, and the substrate graphite powder is prepared by steps such as dry mixing, heating pinch and crushing. Rate and antioxidant performance.
It significantly improves the thermal guidance rate of spherical fuel components, reached 40-45W/mk (1000 ° C), and improved the antioxidant performance, and improved the safety and performance of high-temperature air-cooled reactors.
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of high temperature gas-cooled reactors, and more specifically, to a matrix graphite powder for preparing high thermal conductivity fuel elements, and a preparation method and application thereof. Background Art
[0002] Depending on the fuel elements used, high-temperature gas-cooled reactors can be divided into prismatic reactors and pebble bed reactors. The latter uses spherical fuel elements. Germany's AVR and THTR, China's HTR-10 and HTR-PM all use spherical fuel elements. It mainly consists of two parts: a fuel zone with a diameter of about 50 mm and a 5 mm thick fuel-free shell. The components mainly include TRISO-coated fuel particles and matrix graphite, of which the mass and volume of matrix graphite account for more than 90%. Since the matrix graphite plays an important role in heat transfer in the fuel element, the heat released by the uranium dioxide particles needs to be transferred to the helium coolant. The better the thermal conductivity of the matrix graphite, the more conducive it is to the performance of the fuel element. Therefore, thermal conductivity is one of the key properties for evaluating whether the matrix graphite is qualified.
[0003] The pebble bed modular high temperature gas-cooled reactor requires that the thermal conductivity of the matrix graphite at 1000°C should be ≥25W / mK. At present, the raw materials for manufacturing the matrix graphite of spherical fuel elements are made of about 64% natural graphite powder, 16% artificial graphite powder and 20% resin binder, also known as A3-3 matrix graphite powder. Among them, the commonly used resin binder is phenolic resin, but phenolic resin is difficult to graphitize, resulting in low thermal conductivity of the matrix graphite. The main reason why the existing technology uses phenolic resin as a binder is that phenolic resin can achieve sufficient purity, while other binders such as coal tar contain too many impurities, which will affect the purity of the matrix graphite. The artificial graphite powder in the A3-3 matrix graphite is generally made of asphalt coke, which is ordinary asphalt coke, and its microcrystalline arrangement orientation is low, so its thermal conductivity is also low.
[0004] Therefore, in the prior art, artificial graphite and resin binder in the matrix graphite are the main bottlenecks restricting further improvement of the thermal conductivity of the matrix graphite. Summary of the invention
[0005] In view of the deficiencies of the above-mentioned prior art, the present application provides a matrix graphite powder for preparing a high thermal conductivity fuel element, and a preparation method and application thereof. The raw materials of the matrix graphite powder in the present application include high-purity natural graphite powder, high-purity needle coke powder and high-purity asphalt. The matrix graphite powder is prepared using high-purity asphalt as a binder, which not only meets the purity requirements, but also has the characteristics of high graphitization degree and better oxidation resistance, and can significantly improve the thermal conductivity of the matrix graphite for spherical fuel elements.
[0006] In order to achieve the above-mentioned objectives, in the first aspect, the present application provides a base graphite powder for preparing a high thermal conductivity fuel element, the raw materials including high-purity natural graphite powder, high-purity needle coke powder and high-purity asphalt, and the ash content of the high-purity natural graphite powder, high-purity needle coke powder and high-purity asphalt are all less than 50ppm.
[0007] Furthermore, the total boron equivalent of the high-purity natural graphite powder is less than 1ppm, D 50 20-30μm, specific surface area ≥4m 2 / g.
[0008] Furthermore, the total boron equivalent of the high-purity needle coke powder is less than 1 ppm, D 50 15-30μm, specific surface area ≥1m 2 / g.
[0009] Furthermore, the total boron equivalent of the high-purity asphalt is less than 1 ppm, the softening point is 100-120° C., the quinoline insoluble matter content is 0.1-15%, and the coking value is greater than 60%.
[0010] Furthermore, the ratio of high-purity natural graphite powder to high-purity needle coke powder is 4-5:1 by weight.
[0011] Furthermore, the high-purity asphalt is petroleum asphalt or liquid coal asphalt; the mass of the high-purity asphalt is 25-35% of the total mass of the mixed dry powder of high-purity natural graphite powder and high-purity needle coke powder.
[0012] In a second aspect, the present application provides a method for preparing a matrix graphite powder for a high thermal conductivity fuel element, comprising the following steps:
[0013] Step S1: respectively obtaining high-purity natural graphite powder, high-purity needle coke powder and high-purity asphalt;
[0014] Step S2: dry-mixing high-purity natural graphite powder and high-purity needle coke powder to obtain a mixed dry powder;
[0015] Step S3: adding liquid high-purity asphalt to the mixed dry powder obtained in step S2, kneading to obtain a paste, cooling and then crushing to obtain the paste.
[0016] Furthermore, the method for preparing high-purity asphalt in step S1 is: using coal tar pitch with quinoline insoluble content <15% and ash content <1000ppm as raw material, adopting supercritical extraction, solvent centrifugation or hot melt filtration to remove impurities in the raw material, and then heat-treating the asphalt after impurity removal by thermal polymerization to obtain high-purity asphalt with ash content <50ppm.
[0017] Furthermore, the specific method of the thermal polymerization method is to place the asphalt after removing impurities in a heating reactor, heat it to 350-450°C at a heating rate of 0.5-2°C / min under a nitrogen atmosphere, and take it out after keeping it warm for 1-5 hours.
[0018] Furthermore, the specific method of mixing in step S2 is to charge the high-purity natural graphite powder and the high-purity needle coke powder into a conical mixer according to the mass ratio, and mix for 1-2 hours.
[0019] Furthermore, in step S3, the kneading temperature is 150-200° C., and the kneading time is 2-3 h.
[0020] Furthermore, after the pulverization in step S3, the product is sieved through a 100-150 mesh standard sieve.
[0021] In a third aspect, the present invention provides a high thermal conductivity fuel element, which is prepared using the above-mentioned matrix graphite powder, and the thermal conductivity of the high thermal conductivity fuel element is 40-45W / mK (1000°C).
[0022] The technical solution provided by this application has at least the following beneficial effects compared with the prior art:
[0023] 1) The present application adopts high-purity asphalt as a binder, which has the property of easy graphitization and can effectively improve the graphitization degree of the matrix graphite of the spherical fuel element of the high-temperature gas-cooled reactor; the fuel element made of the matrix graphite powder described in the present application has a graphitization degree of ≥98%, which is beneficial to improve the thermal conductivity of the spherical fuel element.
[0024] 2) The present application adopts high-purity needle coke powder to replace artificial graphite. Needle coke is stretched by air flow during coking. Its graphite crystallites are arranged in the same direction and are typical easily graphitized carbon. After graphitization, it has strong thermal conductivity, which can further improve the thermal conductivity of the fuel element. The fuel element made of the matrix graphite powder described in the present application has an average thermal conductivity of 40-45W / mK (1000℃), which is significantly higher than the 35.5W / mK (1000℃) of the existing A3-3 matrix graphite.
[0025] 3) The asphalt-derived carbon formed by the high-purity asphalt used in the present application has better antioxidant properties and can improve the antioxidant properties of the fuel elements; the fuel elements made of the matrix graphite powder described in the present application have an oxidation reaction activation energy of about 185-190 kJ / mol, which is significantly higher than the 176 kJ / mol of the A3-3 matrix graphite with resin as the binder, which is beneficial to improving the safety of high-temperature gas-cooled reactors. DETAILED DESCRIPTION
[0026] In order to enable those skilled in the art to understand the present application more clearly, the present application is further described in detail below in conjunction with examples. However, it should be understood that the following examples are only preferred implementation methods of the present application, and the scope of protection required by the present application shall be based on the scope defined in the claims.
[0027] In the description of the present invention, it should be noted that, if the specific conditions are not specified in the examples, the experiments were carried out according to conventional conditions or the conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturer is not specified, are all conventional products that can be purchased commercially.
[0028] <Example>
[0029] Example 1
[0030] This embodiment provides a matrix graphite powder for preparing a high thermal conductivity fuel element, wherein the raw materials include high-purity natural graphite powder, high-purity needle coke powder and high-purity asphalt, wherein the ash content of the high-purity natural graphite powder, high-purity needle coke powder and high-purity asphalt is less than 50ppm; the total boron equivalent of the high-purity natural graphite powder is less than 1ppm, and D 50 25.9μm, specific surface area 4.48m 2 / g,; the total boron equivalent of the high-purity needle coke powder is less than 1ppm, D 50 The surface area is 19.2 μm and the specific surface area is 1.49 m 2 / g; calculated by mass ratio, the ratio of high-purity natural graphite powder to high-purity needle coke powder is 4:1; calculated by mass percentage, the mass ratio of high-purity asphalt to the mixed dry powder of high-purity natural graphite powder and high-purity needle coke powder is 25%.
[0031] The above-mentioned matrix graphite powder is prepared by the following method:
[0032] Step S1: respectively obtaining high-purity natural graphite powder, high-purity needle coke powder and high-purity asphalt;
[0033] The method for preparing high-purity asphalt is as follows: obtaining coal tar pitch with a quinoline insoluble content of less than 15% and an ash content of less than 1000 ppm; purifying the coal tar pitch by supercritical extraction to remove impurity ash, reducing the ash content to less than 50 ppm, and then increasing the secondary quinoline insoluble content in the asphalt by thermal polymerization to increase the softening point and coking value of the high-purity asphalt; the specific method of the thermal polymerization method is as follows: placing the asphalt obtained by supercritical extraction in a heating reactor, heating it to 350°C at a heating rate of 1°C / min under a nitrogen atmosphere, and taking it out after keeping it warm for 2 hours to obtain a high-purity asphalt with a softening point of 117°C, a quinoline insoluble content of 5%, and a coking value of 62%;
[0034] Step S2: dry-mixing high-purity natural graphite powder and high-purity needle coke powder; specifically, mixing in a conical mixer for 1 hour;
[0035] Step S3: adding liquid high-purity asphalt to the mixed dry powder of high-purity natural graphite powder and high-purity needle coke powder, heating to 200° C. and kneading for 2 hours to obtain a paste; cooling the paste and then crushing it, and passing it through a 100-mesh standard sieve.
[0036] The spherical fuel element made of the above-mentioned matrix graphite powder is obtained by molding and heat treatment. The specific steps are: loading the matrix graphite powder and fuel particles into a spherical silicone rubber mold, pre-molding at a pressure of 5MPa to obtain a spherical core, then transferring the spherical core to another spherical silicone rubber mold, and filling the matrix graphite powder around the spherical core, isostatically pressing at a pressure of 300MPa to obtain a spherical fuel element raw product, and then carbonizing at 850°C, purifying at 1950°C and turning to obtain a spherical fuel element finished product; the properties of the matrix graphite of the spherical fuel element are: bulk density 1.75g / cm 3 , graphitization degree 98.9%, thermal conductivity 42.5W / mK at 1000℃, thermal expansion anisotropy ratio 1.07, oxidation reaction activation energy 190kJ / mol.
[0037] Example 2
[0038] This embodiment provides a matrix graphite powder for preparing a high thermal conductivity fuel element, which is different from the embodiment 1 in that, by mass ratio, the ratio of high-purity natural graphite powder to high-purity needle coke powder in the mixed dry powder is 5:1. By mass percentage, the mass ratio of high-purity asphalt to the mixed dry powder is 35%. The remaining steps are the same as those in the embodiment 1.
[0039] After forming and heat treatment, a spherical fuel element made of the matrix graphite powder of this embodiment is obtained (the method is the same as that of Example 1), and the properties of the matrix graphite of the spherical fuel element are measured as follows: bulk density 1.75 g / cm 3 , graphitization degree 98.5%, thermal conductivity 43.1W / mK at 1000℃, thermal expansion anisotropy ratio 1.08, oxidation reaction activation energy 189kJ / mol.
[0040] Comparative Example 1
[0041] This comparative example provides a method for preparing a conventional A3-3 matrix graphite powder, which is different from Example 1 in that this comparative example does not use high-purity needle coke and high-purity asphalt, but uses high-purity artificial graphite with an ash content of less than 50ppm and a total boron equivalent of less than 1ppm and high-purity phenolic resin, and the high-purity phenolic resin is dissolved in anhydrous ethanol at a concentration of 50%. In terms of mass ratio, the ratio of high-purity natural graphite powder to high-purity artificial graphite powder in the mixed dry powder is 4:1; in terms of mass percentage, the mass ratio of high-purity phenolic resin to the mixed dry powder is 25%.
[0042] The above-mentioned matrix graphite powder is prepared by the following method:
[0043] Step S1: respectively obtaining high-purity natural graphite powder, high-purity artificial graphite powder and high-purity phenolic resin;
[0044] Step S2: dry-mixing high-purity natural graphite powder and high-purity needle coke powder; specifically, mixing in a conical mixer for 1 hour;
[0045] Step S3: adding phenolic resin solution to the mixed dry powder of high-purity natural graphite powder and high-purity artificial graphite powder, kneading at room temperature for 2 hours to obtain a paste; drying the paste, crushing it, and passing it through a 100-mesh standard sieve.
[0046] After forming and heat treatment, a spherical fuel element made of the matrix graphite powder of this comparative example was obtained (the method is the same as that of Example 1), and the properties of the matrix graphite of the spherical fuel element were measured as follows: bulk density 1.74 g / cm 3 , graphitization degree 97.2%, thermal conductivity 35.5W / mK at 1000℃, thermal expansion anisotropy ratio 1.07, oxidation reaction activation energy 176kJ / mol.
[0047] Comparative Example 2
[0048] This comparative example provides a matrix graphite powder for preparing a high thermal conductivity fuel element. The difference between this comparative example and Example 1 is that this comparative example does not use high-purity asphalt, but uses high-purity phenolic resin with an ash content of less than 50ppm and a total boron equivalent of less than 1ppm. The high-purity phenolic resin is dissolved in anhydrous ethanol at a concentration of 50%. In terms of mass ratio, the ratio of high-purity natural graphite powder to high-purity needle coke powder in the mixed dry powder is 4:1. In terms of mass percentage, the mass ratio of high-purity phenolic resin to the mixed dry powder is 25%. The preparation method of the matrix graphite powder of this comparative example is the same as that of comparative example 1.
[0049] After forming and heat treatment, a spherical fuel element made of the matrix graphite powder of this comparative example was obtained (the method is the same as that of Example 1), and the properties of the matrix graphite of the spherical fuel element were measured as follows: bulk density 1.73 g / cm 3 , graphitization degree 97.8%, thermal conductivity 38.3W / mK at 1000℃, thermal expansion anisotropy ratio 1.09, oxidation reaction activation energy 179kJ / mol.
[0050] Comparative Example 3
[0051] This comparative example provides a matrix graphite powder for preparing a high thermal conductivity fuel element, which is different from Example 1 in that this comparative example does not use high-purity needle coke powder, but uses high-purity artificial graphite powder with an ash content of <50ppm and a total boron equivalent of <1ppm, and the rest is the same as Example 1. In terms of mass ratio, the ratio of high-purity natural graphite powder to high-purity artificial graphite powder in the mixed dry powder is 4:1; in terms of mass percentage, the mass ratio of high-purity asphalt to the mixed dry powder is 25%.
[0052] After forming and heat treatment, a spherical fuel element made of the matrix graphite powder of this comparative example was obtained (the method is the same as that of Example 1), and the properties of the matrix graphite of the spherical fuel element were measured as follows: bulk density 1.73 g / cm 3 , graphitization degree 98.1%, thermal conductivity 40.5W / mK at 1000℃, thermal expansion anisotropy ratio 1.08, oxidation reaction activation energy 186kJ / mol.
[0053] Comparative Example 4
[0054] This comparative example provides a base graphite powder for preparing high thermal conductivity fuel elements. The difference between this comparative example and Example 1 is that the asphalt obtained by supercritical extraction is not further heat treated in this comparative example. The softening point of the obtained high-purity asphalt is 72°C, the quinoline insoluble matter content is 0.1%, and the coking value is 42%; the rest is the same as Example 1.
[0055] The spherical fuel element made of the matrix graphite powder of this comparative example was obtained by molding and heat treatment (the method is the same as that of Example 1), and the properties of the matrix graphite of the spherical fuel element were measured as follows: bulk density 1.53 g / cm 3 , graphitization degree 97.8%, thermal conductivity 39.5W / mK at 1000℃, thermal expansion anisotropy ratio 1.08, oxidation reaction activation energy 162kJ / mol.
[0056] The above-mentioned specific embodiments of the present application are merely preferred embodiments for explaining the present application, and are not limitations of the present application. After reading this specification, those skilled in the art may make modifications without creative contribution as needed. However, any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the protection scope of the present application.
Claims
1. A matrix graphite powder for preparing a high thermal conductivity fuel element, characterized in that: The raw materials include high-purity natural graphite powder, high-purity needle coke powder and high-purity asphalt, and the ash contents of the high-purity natural graphite powder, high-purity needle coke powder and high-purity asphalt are all less than 50ppm.
2. The matrix graphite powder for preparing a high thermal conductivity fuel element according to claim 1, characterized in that: The total boron equivalent of the high-purity natural graphite powder is less than 1ppm, D 50 20-30μm, specific surface area ≥4m 2 / g.
3. The matrix graphite powder for preparing a high thermal conductivity fuel element according to claim 1, characterized in that: The total boron equivalent of the high-purity needle coke powder is less than 1ppm, D 50 15-30μm, specific surface area ≥1m 2 / g.
4. The matrix graphite powder for preparing a high thermal conductivity fuel element according to claim 1, characterized in that: The high-purity asphalt has a total boron equivalent of less than 1 ppm, a softening point of 100-120° C., a quinoline insoluble matter content of 0.1-15%, and a coking value of more than 60%.
5. The matrix graphite powder for preparing a high thermal conductivity fuel element according to claim 1, characterized in that: By weight, the ratio of high-purity natural graphite powder to high-purity needle coke powder is 4-5:
1.
6. The matrix graphite powder for preparing a high thermal conductivity fuel element according to claim 1, characterized in that: The high-purity asphalt is petroleum asphalt or coal asphalt; the mass of the high-purity asphalt is 25-35% of the total mass of the mixed dry powder of high-purity natural graphite powder and high-purity needle coke powder.
7. The method for preparing a matrix graphite powder for preparing a high thermal conductivity fuel element according to any one of claims 1 to 6, characterized in that: The following steps are involved: Step S1: respectively obtaining high-purity natural graphite powder, high-purity needle coke powder and high-purity asphalt; Step S2: dry-mixing high-purity natural graphite powder and high-purity needle coke powder to obtain a mixed dry powder; Step S3: adding liquid high-purity asphalt to the mixed dry powder obtained in step S2, kneading to obtain a paste, cooling and then crushing to obtain the paste.
8. The method for preparing a matrix graphite powder for preparing a high thermal conductivity fuel element according to claim 7, characterized in that: The method for preparing high-purity asphalt in step S1 is: using asphalt with quinoline insoluble content <15% and ash content <1000ppm as raw material, removing impurities in the raw material by supercritical extraction, solvent centrifugation or hot melt filtration, and then heat treating the asphalt after impurities are removed by thermal polymerization to obtain high-purity asphalt with ash content <50ppm.
9. The method for preparing a matrix graphite powder for preparing a high thermal conductivity fuel element according to claim 8, characterized in that: The specific method of the thermal polymerization method is to place the asphalt after removing impurities in a heating reactor, heat it to 350-450°C at a heating rate of 0.5-2°C / min under a nitrogen atmosphere, and take it out after keeping it warm for 1-5 hours.
10. A high thermal conductivity fuel element, prepared using the matrix graphite powder according to any one of claims 1 to 6, wherein the thermal conductivity of the high thermal conductivity fuel element at 1000°C is 40-45 W / mK.
Citation Information
Patent Citations
Process and equipment for producing graphite dust
CN101318648A
High-heat conduction graphitized carbon material and method of manufacturing the same
CN101508433A
High purity nuclear graphite
CN101535178A
Preparation method of nuclear graphite material
CN107857261A
Novel isotropic nuclear-grade graphite material and preparation method thereof
CN111362698A